1984
DOI: 10.1007/bf00252327
|View full text |Cite
|
Sign up to set email alerts
|

Localization to chromosomes of structural genes for the major protease inhibitors of barley grains

Abstract: Wheat-barley chromosome addition lines were compared by isoelectric focusing of protein extracts to identify chromosomes carrying loci for the major immunochemically distinct protease inhibitors of barley grains. Structural genes for the following inhibitors were localized: an inhibitor of both endogenous α-amylase 2 and subtilisin (ASI) on chromosome 2, two chymotrypsin/subtilisin inhibitors (CI-1 and CI-2) on chromosome 5 (long arm) and the major trypsin inhibitor (TI-1) on chromosome 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The trypsin inhibitor sequenced by Odani et al (1983) and protein CMe (Salcedo et al 1984) had been found to be identical (Lázaro et al 1985), and the corresponding gene had been located in chromosome 3H (Hejgaard et al 1984;Salcedo et al 1984). Besides trypsin inhibitor CMe, a second homologous trypsin inhibitor, designated CMe, had been identified in barley endosperm (Barber et al 1986) and its gene assigned to chromosome 7H (Salcedo et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trypsin inhibitor sequenced by Odani et al (1983) and protein CMe (Salcedo et al 1984) had been found to be identical (Lázaro et al 1985), and the corresponding gene had been located in chromosome 3H (Hejgaard et al 1984;Salcedo et al 1984). Besides trypsin inhibitor CMe, a second homologous trypsin inhibitor, designated CMe, had been identified in barley endosperm (Barber et al 1986) and its gene assigned to chromosome 7H (Salcedo et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…1. This chromosome had been previously proposed as the site of gene CMe, based on the electrophoretic analysis of the protein (Salcedo et al 1984;Hejgaard et al 1984). The insert of clone X CMe was subcloned and sequenced (Fig.…”
Section: Bgliimentioning
confidence: 99%
“…It has previously been shown that the mutant has a deletion of most or all of the B hordein genes [40]. Since the CI-1 genes have been mapped to the long arm of chromosome 5 [28], it is unlikely that their expression is directly affected by the mutation. It is probable that the increased CI-1 compensates for the decreased B hordein because of an excess of soluble amino acids which accumulate in the seeds of mutant 56.…”
Section: Expression O F Ci-1 In Normal and Mutant Barleysmentioning
confidence: 99%
“…These traits are a potentially valuable resource of useful genes for the genetic improvement of wheat (Triticum aestivum, 2n = 42, AABBDD), a relative of barley. It has been reported that the basi gene on the long arm of barley chromosome 2H confers reduced precocious germination by coding an endogenous, bifunctional α-amylase/subtilisin inhibitor to modulate α-amylase activity (Hejgaard et al, 1984). It is especially effective at inhibiting wheat α-amylase activity (Henry et al, 1992).…”
Section: Introductionmentioning
confidence: 99%